2014
DOI: 10.1007/s00253-014-5759-7
|View full text |Cite
|
Sign up to set email alerts
|

An extracytoplasmic function sigma factor, σ25, differentially regulates avermectin and oligomycin biosynthesis in Streptomyces avermitilis

Abstract: σ(25) is an extracytoplasmic function (ECF) σ factor in the bacterium Streptomyces avermitilis that plays a differential regulatory role in avermectin and oligomycin biosynthesis. Gene deletion, complementation, and overexpression experiments showed that σ(25) inhibited avermectin production but promoted oligomycin production. σ(25) indirectly inhibited avermectin production by affecting the transcription of the pathway-specific activator gene aveR, whereas it directly activated oligomycin production by initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 32 publications
0
47
0
Order By: Relevance
“…Among 350 putative SAV742 targets having regulatory function, three have been reported to negatively regulate avermectin production: avaR1 (sav_3705 , encoding a putative gamma-butyrolactone receptor protein)3435, sig25 (sav_3351 , encoding an ECF sigma factor) and smrA (sav_3352 , encoding a two-component system response regulator)36. EMSAs showed that SAV742 bound specifically to the avaR1 promoter region and sig25-smrA bidirectional promoter region (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Among 350 putative SAV742 targets having regulatory function, three have been reported to negatively regulate avermectin production: avaR1 (sav_3705 , encoding a putative gamma-butyrolactone receptor protein)3435, sig25 (sav_3351 , encoding an ECF sigma factor) and smrA (sav_3352 , encoding a two-component system response regulator)36. EMSAs showed that SAV742 bound specifically to the avaR1 promoter region and sig25-smrA bidirectional promoter region (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The obtained PCR product was cut with Bam HI/ Hin dIII and ligated into expression vector pET-28a (+) to generate pET-742, which was then transformed into E. coli BL21 (DE3) for overexpression of N-terminal His 6 -tagged SAV742 recombinant protein. Following induction by 0.2 mM IPTG, bacteria containing His 6 -SAV742 were collected, washed, resuspended in a lysis buffer36, and sonicated on ice. Soluble His 6 -SAV742 was purified by Ni-NTA agarose chromatography (Qiagen) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…3A. AveT and AveM have opposing effects on avermectin production, and the other transcriptional regulators affect aveR expression (27,28,47), resulting jointly in a gradual increase in the level of avermectin production in cells. The present finding that a late intermediate in the avermectin pathway acts as a regulator of its own production suggests a positive-feedback regulatory mechanism that ensures the irreversible production of avermectins and their appropriate concentration in cells.…”
Section: Discussionmentioning
confidence: 99%
“…157 Interestingly, ECF σ 25 in S. avermitilis differentially regulates production of two macrolides oligomycin and avermectin, where overexpression of sig25 increases oligomycin production but decreases avermectin titer. 159 Given that σ 25 directly binds to promoter regions of oligomycin biosynthetic genes, it is likely that the associated reduction in avermectin production is due to competition for common precursors. 159 From a host engineering perspective, sigma factors function as resource allocators to distribute the transcriptional resources (e.g.…”
Section: Strategies For Strain Improvementmentioning
confidence: 99%
“…159 Given that σ 25 directly binds to promoter regions of oligomycin biosynthetic genes, it is likely that the associated reduction in avermectin production is due to competition for common precursors. 159 From a host engineering perspective, sigma factors function as resource allocators to distribute the transcriptional resources (e.g. RNAP) within the cell.…”
Section: Strategies For Strain Improvementmentioning
confidence: 99%